Bisguanidiums catalyzed enantioselective oxidation of sulfides to sulfoxides - Ye, Xinyi (2015)
Chiral sulfoxides are the functional groups in many drugs. In synthesis, the most direct and economic way is oxidized by oxidants. Contemporarily, the most meritorious and practical oxidation method was improved according to Sharpless-Kagan’s system. However, it has been serving us for more than three decades, and it is no longer a sufficient method to satisfy the environmental problem. For instance, in most of cases, an environmental benign oxidant hydrogen peroxide is less-favoured than UHP (urea hydrogen peroxide) and CHP (cumyl hydroperoxide) in homogenous system. Additionally, metal complex coordinated with organic ligands is hard to be removed from organic phase, which causes a lot of trouble in processing procedure. Thus, organocatalyzed heterogeneous oxidation realized by hydrogen peroxide is put forward by using our phase-transfer catalyst. Another associated catalytic oxygen transfer reagent is tungstate oxide anion. When developing this new methodology for oxidation of chiral sulfoxides, both chemoselectivity and enantioselectivity should be considered. Our novel catalyst solves the former problem by oxygen transfer anion, and the later problem is solved by our chiral cation. This process would be leaded by electron force and π-π interaction between substrates and catalyst as proposed.